Postharvest features of chrysanthemum cut flowers as affected by different chemicals - Hassan, F.; Schmidt, G. (International Journal of Horticultural Science, 2004)
Cut flowers of Chrysanthemum morifolium RAM cv. Suny Reagan were treated with different concentrations of 8- hydroxyquinoline sulfate (8-HQS), silver thiosulfate (STS) and 1-methylcyclopropene (1-MCP) in order to improve the post production quality. 8-HQS was used at 200 and 400 ppm with or without sucrose at 50 O. STS was used at 0.2, and 0.4 mM with or without sucrose at 50 g/1 1-MCP was used at 0.3, 0.5 and 0.7 g/m3 for 6h.All the treatments of 8-HQS prolonged the vase life and minimized the percentage of weight loss of chrysanthemum cut flowers compared to the control. The vase life was larger when sucrose not combined with 8-HQS. The best treatment of 8-1-IQS was 400 ppm 8-HQS without sucrose. STS treatment led to prolong the vase life and minimized the percentage of weight loss comparing to the control. In addition, the effect was better when sucroseas was added to STS. The treatment of STS at 0.4 mM + 50 g/I sucrose was the best one. 1-MCP treatment increased the vase life and lowered the percentage of weight loss at any level comparing with untreated control. The best treatment in this concern was 1-MCP at 0.5 g/m3 for 6h. The chlorophyll content (chl.a and chl.b) of the leaves for the best treatment of each chemical was higher than that of the control. The treatment of 1-MCP at 0.5 g/m3 6h gave the best results in this respect.